Management of Academic Services in Building Student Satisfaction in Private Islamic Religious College: A Descriptive Qualitative Analysis Study at STAI Al Musaddadiyah, STAI Darul Arqam, And Stai Persis in Garut Regency - Yufi Mohammad Nasrullah; Tb. Abin Syamsudin; Sofyan Sauri; Waska Warta (Journal of Social Science, 2022)
This research is motivated by student dissatisfaction with academic services, who are often dissatisfied with the academic services provided, such as facilities and staff performance that are not in line with the expectations of students as customers. This study aims to provide an overview of academic service management in building student satisfaction which includes: (1) Planning; (2) Implementation; (3) Evaluation; (4) Results and achievements; (5) Supporting factors; (6) Inhibiting factors; (7) Hope; (8) Solution. This research method used a descriptive method with a qualitative approach and case study design, in the process by observation, interviews and documentation. The management theory appropriate for the service is the modern management theory. Terry. G. clarifies these management functions in four parts, namely as follows: planning (Planning), organizing (Organizing), actuating, and controlling (Controlling). The results of the study show that there was a different understanding and implementations where STAI Al Musaddadiyah established the process of academic services in the expanding student’s satisfaction which was supported by an academic service information system, STAI Darul Arqam was supported by an integrated program from the centre, a program of learning supports STAI Persis. All components, policymakers, authorities, and interested parties were required to support the realization of good quality academic services. The achievement of quality academic services would build creative, innovative, productive resources and had the value of independence to build self-potential in creating a quality culture in private Islamic religious colleges